New forms of local governance : a theoretical and empirical analysis of municipal corporations in Portugal - Tavares, António F. (2010)
What factors influence local governments to rely on municipal corporations to provide public services? This article seeks to identify which factors lead local governments to use local corporate public sector organizations, particularly municipal corporations, for service delivery. Based on the ideas of the neo-institutionalism approach to public administration developed by Murray Horn (1995), we argue that local officials trade-off bureaucratic costs of in-house production with agency costs of external delegation to municipal corporations when deciding how to deliver local public services. Econometric models are employed to test this explanation for the adoption of municipal corporations by the 278 Portuguese local governments. The results indicate that organizational size, financial independency, and fiscal surplus, as well as ideological concerns and the activity of local interest groups, drive choices of local governance structures.